A Portrait of Higher Education Students’ Experiences of doing Informal Digital Learning of English (IDLE) Speaking Practices in Indonesia - Rahmawati, Rani; Drajati, Nur Arifah; Asib, Abdul (English Education: Jurnal Tadris Bahasa Inggris, 2019)
This paper aimed to explore the experiences of higher education students on Informal Digital Learning of English (IDLE) speaking practices and their personal insight of IDLE influences on their speaking skill. Through this study it is revealed that language learning style on the case of IDLE speaking practice was successfully explained on the practice. This research used interview and participants’ observation. For analyzing the data, the researcher used narrative inquiry model including data collection, data transcription and reporting the narrative study. The participants were two undergraduate female students. Both of them have an experience to go abroad and have a lot of online foreigner friends by IDLE. The result explained that participants have different purposes of practiced IDLE speaking and the way they practiced IDLE speaking. These practices also influenced their speaking aspects such as vocabulary, grammar, fluency, comprehension, and pronunciation. This new learning strategy in an informal context helps them as university students to love their process of learning a language.